(untitled) (DAPesquisa, 2020)
This paper presents a teorical and conceptual review about actor’s training in performing arts for technical and artistic development with a view to potentializing and expanding the vocal body actions. The phenomenological reduction (époché) is approached as a reflexion’s key concept in liberation of the vocal body’s automatisms. It is focused on scenic artists interested in a theatrical practice inspired by Antonin Artaud. The question is to investigate the possibilities of improvisation, devir-conscious creation and suspension in the research for a Vocal Body without Organs